Feasibility and case studies on converting small hydropower stations to pumped storage - Yangqing Dan; Qingyue Chen; Daren Li; Wenhuan Bai; Weiming Zhou; Anyu Yang; Jia Yang (Scientific Reports)
Abstract Hydropower, as a controllable energy source, plays a crucial role in supporting essential functions such as peak shaving, frequency regulation, and load reserve within modern power systems, thereby enhancing the overall economic efficiency and safety of these systems. This study utilizes data from small hydropower stations and advanced software algorithms to preliminarily evaluate the feasibility of converting conventional small hydropower stations in Zhejiang Province into pumped storage hydropower stations, with the province serving as the focal research area. Through comprehensive analysis and field investigations, Jiangshantou Hydropower Station has been selected as the pilot site for this conversion initiative. The proposed conversion scheme has been assessed, and predictions regarding annual operating hours, power generation, and energy consumption have been formulated. The analysis indicates that Jiangshantou Pumped Storage Hydropower Station will serve as the primary mechanism for power regulation. Furthermore, a small-scale integrated hydropower-wind-solar power system is proposed to ensure stable system output, improve the input-output ratio, and enhance the efficiency of renewable energy utilization. Optimal locations for development have been identified, including a 6-hectare photovoltaic installation situated approximately 3.5 km from the dam, alongside a nearby elevated site suitable for wind energy generation. Tools such as SolarGIS and the Global Wind Atlas were employed to assess the solar and wind resources in the area, revealing that the site possesses abundant and stable solar resources, as well as favorable indicators for wind energy, making it an ideal candidate for photovoltaic and wind energy development. This research establishes a comprehensive framework for the conversion of conventional hydropower stations into pumped storage facilities, offering a model for medium-small scale pumped storage and distributed generation technologies. It is recommended to implement photovoltaic forecasting systems at the PV site to achieve more precise control over photovoltaic output and enhance the responsiveness of the pumped storage station to fluctuations in solar power.